Job Satisfaction in Fisheries Compared - Pollnac, Richard (Springer Netherlands, 2012)
This article draws comparative lessons from seven job satisfaction studies on marine capture fishing that were recently carried out in nine countries and three geographical regions—Asia, Africa, and the Caribbean. The seven studies made use of an identical job satisfaction assessment tool and present information on a selection of métiers mainly in the small-scale and semi-industrial fishing sectors. The responses manifest statistically significant geographical variation. Multidimensional plots and cluster analyses lead the authors to identify three clusters: (1) Southeast Asian (Vietnam and Thailand); (2) Caribbean (Belize, Nicaragua, Dominican Republic) and (3) Afro-Indian (Senegal, Guinea Bissau, and India). Jamaica is a significant outlier. On a general level, the authors conclude that fishers who report that they are not interested in leaving the occupation of fishing score higher on three traditional job satisfaction scales—basic needs, social needs and self actualization. Those who say they would leave fishing for another occupation are younger, have less fishing experience and smaller households. The latter findings are of relevance with regard to the pressing need, felt by fisheries managers, to move fishers out of the fishery.